A method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene sulphuric acid

Through the pressure secondary reverse leaching and nanofiltration membrane separation technology of spodumacoustic acid, the problems of high energy consumption and low lithium recovery in the lithium extraction process of spodumacoustic acid in the traditional sulfuric acid roasting method are solved, and efficient lithium recovery is achieved and maximize resource utilization, simplify process flow and reduce production costs.

CN115893455BActive Publication Date: 2024-12-20SICHUAN COMPLIANCE LITHIUM MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202211459583.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2024-12-20
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

In the process of lithium extraction with spodumene ore, the traditional sulfuric acid roasting method has problems such as high energy consumption, long production process, low lithium recovery rate, inability to classify recycling of by-products, gas pollution and high production costs.

Method used

The pressure secondary reverse leaching method of spodumene sulfuric acid is adopted. The leaching rate and recovery rate of lithium are improved by post-calcination ball milling, secondary reverse leaching of sulfuric acid, nanofiltration membrane separation and chemical impurity removal, and lithium and aluminum are deposited by soda ash. Reactions achieve maximum utilization of resources.

Benefits of technology

The process flow is simplified, the lithium loss rate and production cost are reduced, the lithium recovery rate and the pH value of the leaching solution are improved, and the by-product generation and soda ash consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115893455B_ABST
    Figure CN115893455B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid, and belongs to the technical field of lithium carbonate preparation. The method of the present invention comprises: S1: calcining the spodumene raw material, and crushing it to a certain particle size by using a ball mill; S2: slurrying the spodumene after ball milling in step S1 with water, adding sulfuric acid to the slurry for secondary reverse leaching with sulfuric acid, and filtering to obtain secondary leaching liquid and secondary leaching residue. Compared with the traditional process, the method of the present invention has a short process flow, low consumption of soda ash and / or soda ash, small amount of slag generated in the production process, and high recovery rate of metallic lithium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium carbonate preparation and relates to a method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid. Background Art

[0002] Sulfuric acid roasting is a common method used by most companies to prepare lithium carbonate. The production process first uses spodumene (0.7-1.3% Li2O) to obtain lithium concentrate (5-6% Li2O) through a flotation process, and then uses a rotary kiln to perform high-temperature crystal transformation roasting on the spodumene concentrate to transform its crystal phase into β-type. Lithium is extracted through sulfation roasting. Sulfuric acid reacts with alkali metals such as lithium, sodium, and potassium in the ore to generate corresponding sulfates. Lithium is converted into lithium sulfate and leached. After cooling and neutralization, it is filtered to obtain a lithium sulfate solution. Then sodium hydroxide is added for causticization to obtain a sodium sulfate solution, which is then frozen to remove the sodium sulfate to obtain a lithium hydroxide solution. After evaporation and centrifugation, lithium hydroxide is obtained, and then carbon dioxide is introduced into the lithium hydroxide solution to obtain lithium carbonate. This method has the advantages of low energy consumption, small material flow, and high production efficiency. However, the disadvantages of this method are that the production process is long, the consumption of impurity removal auxiliary materials is large, the slag production is large, the recovery rate of lithium is low, the by-products cannot be classified and recycled, and the production cost is high.

[0003] In the traditional sulfuric acid method for lithium extraction from spodumene, sulfur dioxide gas will be produced during the sulfuric acid roasting process after calcination of spodumene, which will pollute the air. The acid-roasted spodumene will be leached once to obtain a leachate with a pH of ≤0.5. A large amount of lime milk is required to neutralize the residual acid and soda ash to adjust the pH and remove impurities, which increases the cost of auxiliary materials. The introduction of calcium will also produce a large amount of calcium sulfate precipitate residue. In addition, a single leaching cannot ensure that a large amount of metals in the spodumene after acidification are leached into the solution, resulting in a large amount of metal loss.

[0004] Therefore, the development of new processes and technologies for extracting lithium from spodumene is of great significance to the development and application of spodumene and the promotion of the development of the new energy lithium battery industry. Summary of the invention

[0005] In order to solve the shortcomings of the existing sulfuric acid roasting and leaching technology, the present invention has developed a method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene sulfuric acid. The method uses spodumene as a raw material, directly calcines, and after ball milling to a certain particle size, sulfuric acid is used for secondary reverse leaching of sulfuric acid, and lithium, aluminum and other metal metals in spodumene are fully leached, and the pH of the leachate obtained by secondary reverse leaching is ≥2.5. After separation by a nanofiltration membrane, the amount of alkali required for chemical impurity removal of the monovalent ion liquid based on lithium sulfate is less, and the obtained impurity removal slag is returned to the front end for secondary reverse leaching of sulfuric acid, which reduces the lithium loss rate. In addition, the polyvalent ion liquid based on aluminum sulfate is chemically precipitated to recycle aluminum ions in the high-valent liquid to maximize resource utilization. The materials used in the present invention are all common industrial products, easy to purchase, cheap, and the entire overall process flow is short, the process is simple, and it is easy to realize industrialization.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid, the method comprising:

[0008] S1: After calcining the spodumene raw material, crush it into a certain particle size using a ball mill;

[0009] S2: adding water to the spodumene ball-milled in step S1 to make a slurry, adding sulfuric acid to the slurry to perform secondary reverse leaching of sulfuric acid, and filtering to obtain a secondary leaching solution and a secondary leaching residue;

[0010] S3: filtering the secondary leaching solution using a nanofiltration membrane to obtain a monovalent ion liquid mainly composed of Li2SO4 and a multivalent ion liquid mainly composed of Al2(SO4)3;

[0011] S4: chemically removing impurities from the monovalent ionic liquid mainly composed of Li2SO4 to obtain a de-impurified liquid and de-impurified residue;

[0012] S5: subjecting the impurity-removed liquid to lithium precipitation reaction using a soda ash solution, and filtering to obtain battery-grade lithium carbonate and lithium precipitation mother liquor;

[0013] S6: using a soda solution to chemically precipitate aluminum using the multivalent ion liquid mainly composed of Al2(SO4)3 to separate aluminum hydroxide and Na2SO4 solution;

[0014] S7: Concentrate and crystallize the lithium precipitation mother liquor and the Na2SO4 solution to obtain Na2SO4.

[0015] As an embodiment of the present invention, in step S1, the calcination temperature is 1000°C to 1200°C, the time is 1 to 5 hours, and the particle size refers to an average particle size less than 74 μm.

[0016] As an embodiment of the present invention, in step S2, the liquid-to-solid mass ratio of the water-adding slurry is 3 to 6:1.

[0017] As an embodiment of the present invention, the method further includes: in step S2, after the water is added and the pulping is performed, a first leaching is performed using new sulfuric acid, and the solid-liquid mixture obtained by the reaction is filtered to obtain a first leaching residue and a first leaching liquid; the first leaching residue is used as active silicon slag to make a soil conditioner or silicon fertilizer for recycling, and the first leaching liquid is used for a second leaching with sulfuric acid; the solid-liquid mixture obtained after the second leaching with sulfuric acid is filtered to obtain the second leaching residue and the second leaching liquid; the second leaching residue is returned as a raw material to the first leaching with sulfuric acid, and the second leaching liquid is used for the nanofiltration membrane separation;

[0018] The amount of new sulfuric acid used in the primary sulfuric acid leaching is 80-120wt% of the theoretical amount calculated based on the main elements participating in the leaching reaction, and the amount of sulfuric acid used in the secondary sulfuric acid leaching is 20-50wt% of the theoretical amount calculated based on the main elements participating in the leaching reaction; the primary acid leaching reaction temperature and the secondary acid leaching reaction temperature are independently selected from any values ​​between 100 and 180° C., the primary acid leaching reaction time and the secondary acid leaching reaction time are independently selected from any values ​​between 1 and 6 hours, and the pH of the secondary leaching solution is ≥2.5.

[0019] As an embodiment of the present invention, in step S3, the nanofiltration membrane separation is multi-stage nanofiltration, the number of stages is 2-7, and the nanofiltration pressure is 2.0-8.0Mpa;

[0020] The mass concentration of Li2SO4 in the monovalent ionic liquid mainly composed of Li2SO4 is 10-80g / L, and the mass concentration of Al2(SO4)3 in the multivalent ionic liquid mainly composed of Al2(SO4)3 is 10-80g / L.

[0021] As an embodiment of the present invention, in step S4, the substance used for the chemical impurity removal is one or more of NaOH, LiOH and Na2CO3, the chemical impurity removal reaction end point pH is 10-12, the temperature is 50-80°C, and the time is 1-3h.

[0022] As an embodiment of the present invention, in step S5, the lithium precipitation reaction temperature is 60-80°C, the amount of soda ash solution used is 100-110wt% of the theoretical amount required for the precipitation reaction of Li and carbonate in the liquid after impurities removal, and the lithium precipitation reaction time is 1-2h.

[0023] As an embodiment of the present invention, in step S6, the endpoint pH value of the chemical aluminum precipitation reaction is 3-7, the temperature is 50-90°C, and the time is 1-2h.

[0024] As an embodiment of the present invention, in step S7, the evaporation concentration temperature is 70 to 110°C, and the crystallization temperature is -5 to 40°C.

[0025] As an embodiment of the present invention, in step S7, the impurity-removed slag in step S4 is returned to the spodumene after ball milling in step S2.

[0026] The above technical solution provided by the present invention brings at least the following beneficial effects:

[0027] The present invention improves the traditional sulfuric acid process, and the raw ore can be directly leached after calcination without flotation. The innovative use of sulfuric acid secondary reverse leaching process makes the amount of leaching slag produced in the leaching process lower, the metal leaching rate in spodumene ore higher, the pH of the leachate is improved, and the amount of soda ash or liquid alkali required for subsequent pH increase is reduced; nanofiltration equipment is introduced into the process to separate the monovalent liquid and the high-valent liquid, and the consumption of soda ash, lithium hydroxide or liquid alkali required for the removal of impurities in the monovalent liquid after separation is lower, and the amount of impurity removal slag is less and circulated in the front-end leaching section, thereby reducing the loss rate of lithium, and the by-product high-valent ion liquid is also processed and recovered. Compared with the traditional process, the present invention has a short process flow, low consumption of soda ash liquid alkali and / or soda ash, small amount of slag produced in the production process, and high recovery rate of metallic lithium. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 The present invention is a schematic flow chart of a method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0030] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0031] The main element (non-oxygen element) analysis results of the spodumene used in the examples of the present invention are shown in Table 1.

[0032] Table 1

[0033]

[0034] Example 1

[0035] A method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid, the detailed steps of which are as follows:

[0036] S1: calcining the spodumene raw material in Table 1 at 1000° C. for 3 h, and ball-milling the calcined spodumene (including the original ore) to an average particle size of less than 74 μm;

[0037] S2: adding water to the spodumene after ball milling in step S1 and slurrying at a liquid-solid mass ratio of 3:1, leaching the slurry once with new sulfuric acid, filtering the solid-liquid mixture obtained by the reaction to obtain a primary leaching residue and a primary leaching liquid; recycling the primary leaching residue, and using the primary leaching liquid for secondary leaching with sulfuric acid; filtering the solid-liquid mixture obtained after the secondary leaching with sulfuric acid to obtain secondary leaching residue and a secondary leaching liquid, and returning the secondary leaching residue as a raw material to the primary leaching with sulfuric acid;

[0038] The amount of new sulfuric acid in the primary sulfuric acid leaching is calculated as 110wt% of the theoretical amount according to the main elements (Li\Na\K\Al\Fe\Ca) involved in the leaching reaction, and the amount of sulfuric acid in the secondary sulfuric acid leaching is calculated as 40wt% of the theoretical amount according to the main elements involved in the leaching reaction (the calculation method of sulfuric acid amount is the same as the primary leaching), the primary leaching reaction temperature and the secondary leaching reaction temperature are both 160°C, the primary leaching reaction time and the secondary leaching reaction time are both 2h, and the solid-liquid mixture obtained by the reaction is filtered to obtain a leachate and a leaching residue, wherein the primary leaching residue is comprehensively recycled, and the pH of the secondary leaching solution is 2.5;

[0039] S3: The secondary leaching liquid obtained in step S2 is filtered by a nanofiltration membrane with a filtration pressure of 3.5 MPa and a stage of 3 to obtain a monovalent ion liquid mainly composed of Li2SO4 and a multivalent ion liquid mainly composed of Al2(SO4)3;

[0040] S4: The monovalent ionic liquid mainly composed of Li2SO4 obtained in step S3 is chemically decontaminated by using a combination of liquid alkali and soda ash to obtain a decontaminated liquid and decontaminated residue, wherein the decontaminated residue is returned to the sulfuric acid reverse secondary leaching process in step S2, and the decontamination reaction endpoint pH is controlled to be 10, the decontamination temperature is 70°C, and the reaction time is 1h;

[0041] S5: adding sodium carbonate to the impurity-removed liquid obtained in step S4 to carry out lithium precipitation reaction to obtain battery-grade lithium carbonate and lithium precipitation mother liquor; the sodium carbonate is calculated based on 105wt% of the theoretical amount required for the precipitation reaction between Li and carbonate in the impurity-removed liquid, the lithium precipitation temperature is 65°C, and the lithium precipitation reaction time is 1h;

[0042] S6: The multivalent ion liquid mainly composed of Al2(SO4)3 obtained in step S2 is subjected to chemical aluminum precipitation using a soda solution, with the temperature controlled at 65°C, the end point pH = 6, and the reaction time 1h, to separate aluminum hydroxide and Na2SO4 solution;

[0043] S7: The lithium precipitation mother liquor obtained in step S5 and the Na2SO4 solution obtained in step S6 are concentrated and crystallized to obtain Na2SO4, the negative pressure evaporation concentration temperature is 90°C, and the crystallization temperature is 20°C.

[0044] The purity of Li2CO3 obtained in this example is 99.58%, and the yield of lithium is 91.28%.

[0045] Example 2

[0046] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0047] In step S1, the calcination temperature is 1050°C and the calcination time is 2h;

[0048] In step S2, water is added to the spodumene after ball milling in step S1 and pulping is performed at a liquid-solid mass ratio of 4:1; wherein, the amount of new sulfuric acid in the primary sulfuric acid leaching is calculated as 100wt% of the theoretical amount according to the main elements (Li\Na\K\Al\Fe\Ca) participating in the leaching reaction, and the amount of sulfuric acid in the secondary sulfuric acid leaching is calculated as 30wt% of the theoretical amount according to the main elements participating in the leaching reaction (the calculation method of sulfuric acid amount is the same as the primary leaching), the primary leaching reaction temperature and the secondary leaching reaction temperature are both 160° C., the primary leaching reaction time and the secondary leaching reaction time are both 2h, and the solid-liquid mixture obtained by the reaction is filtered to obtain a leachate and a leaching residue, wherein the primary leaching residue is comprehensively recycled, and the pH of the secondary leaching solution is 3;

[0049] In step S5, the sodium carbonate is calculated as 108wt% of the theoretical amount required for the precipitation reaction between Li and carbonate in the impurity-removed solution, the lithium precipitation temperature is 70°C, and the lithium precipitation reaction time is 1.5h;

[0050] In step S7, the negative pressure concentration temperature is 95°C and the crystallization temperature is 30°C;

[0051] The purity of Li2CO3 obtained in this example is 99.56%, and the lithium yield is 91.50%.

[0052] Example 3

[0053] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0054] In step S1, the calcination temperature is 1100°C and the calcination time is 1.5h;

[0055] In step S2, water is added to the spodumene after ball milling in step S1 and pulping is performed at a liquid-solid mass ratio of 5:1; wherein, the amount of new sulfuric acid in the primary sulfuric acid leaching is calculated as 120wt% of the theoretical amount according to the main elements (Li\Na\K\Al\Fe\Ca) involved in the leaching reaction, and the amount of sulfuric acid in the secondary sulfuric acid leaching is calculated as 40wt% of the theoretical amount according to the main elements involved in the leaching reaction (the calculation method of sulfuric acid amount is the same as that of the primary leaching), the primary leaching reaction temperature and the secondary leaching reaction temperature are both 170° C., and the primary leaching reaction time and the secondary leaching reaction time are both 1.5h;

[0056] In step S5, the lithium deposition temperature is 75°C and the time is 2h;

[0057] The purity of Li2CO3 obtained in this example is 99.60% and the yield is 90.10%.

[0058] Example 4

[0059] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0060] In step S2, the amount of new sulfuric acid in the primary sulfuric acid leaching is calculated as 90wt% of the theoretical amount according to the main elements (Li\Na\K\Al\Fe\Ca) involved in the leaching reaction, and the amount of sulfuric acid in the secondary sulfuric acid leaching is calculated as 50wt% of the theoretical amount according to the main elements involved in the leaching reaction (the calculation method of sulfuric acid dosage is the same as the primary leaching);

[0061] The purity of Li2CO3 obtained in this example is 99.68% and the yield is 90.20%.

[0062] Example 5

[0063] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0064] In step S5, sodium carbonate is calculated as 110 wt% of the theoretical amount required for the precipitation reaction between Li and carbonate in the liquid after impurities removal, the lithium precipitation temperature is 80° C., and the time is 1.5 h.

[0065] The purity of Li2CO3 obtained in this example is 99.70% and the yield is 90.70%.

[0066] Comparative Example 1

[0067] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0068] S1: The spodumene raw material in Table 1 was calcined at 900° C. for 3 h, and the calcined spodumene (including the original ore) was ball-milled to make the average particle size of the lithium ore less than 74 μm.

[0069] The purity of Li2CO3 obtained in this example is 99.74% and the yield is 53.10%.

[0070] Comparative Example 2

[0071] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0072] S1: The spodumene raw material in Table 1 was calcined at 1300° C. for 3 h, and the calcined spodumene (including the original ore) was ball-milled to make the average particle size of the lithium ore less than 74 μm.

[0073] The purity of Li2CO3 in this embodiment is 99.70% and the yield is 75.10%.

[0074] Comparative Example 3

[0075] Battery-grade lithium carbonate was produced using the method of Example 1, except that:

[0076] In step S2, the amount of new sulfuric acid used in the primary sulfuric acid leaching is calculated as 115wt% of the theoretical amount required based on the main elements (Li\Na\K\Al\Fe\Ca) participating in the leaching reaction, and no secondary leaching is performed. The pH of the obtained leachate is 0.5.

[0077] The purity of Li2CO3 obtained in this example is 99.61% and the yield is 80.6%.

[0078] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for producing battery-grade lithium carbonate by pressurized secondary reverse leaching of spodumene with sulfuric acid, characterized in that: The method comprises: S1: After calcining the spodumene raw material, crush it into a certain particle size using a ball mill; In step S1, the calcination temperature is 1000°C to 1200°C, the time is 1 to 5 hours, and the particle size refers to an average particle size of less than 74 μm; S2: adding water to the spodumene ball-milled in step S1 to make a slurry, adding sulfuric acid to the slurry to perform secondary reverse leaching of sulfuric acid, and filtering to obtain a secondary leaching solution and a secondary leaching residue; In step S2, after the water is added and the pulping is performed, new sulfuric acid is used for primary leaching, and the solid-liquid mixture obtained by the reaction is filtered to obtain primary leaching residue and primary leaching liquid; the primary leaching residue is used as active silicon slag to make soil conditioner or silicon fertilizer for recycling, and the primary leaching liquid is used for secondary leaching with sulfuric acid; the solid-liquid mixture obtained after the secondary leaching with sulfuric acid is filtered to obtain the secondary leaching residue and the secondary leaching liquid; the secondary leaching residue is returned as a raw material to the primary leaching with sulfuric acid; The amount of new sulfuric acid used in the primary sulfuric acid leaching is 80-120wt% of the theoretical amount calculated based on the main elements participating in the leaching reaction, and the amount of sulfuric acid used in the secondary sulfuric acid leaching is 20-50wt% of the theoretical amount calculated based on the main elements participating in the leaching reaction; the primary acid leaching reaction temperature and the secondary acid leaching reaction temperature are independently selected from any value between 100-180°C, the primary acid leaching reaction time and the secondary acid leaching reaction time are independently selected from any value between 1-6h, and the pH of the secondary leaching solution is ≥2.5; S3: filtering the secondary leaching solution using a nanofiltration membrane to obtain a monovalent ion liquid mainly composed of Li2SO4 and a multivalent ion liquid mainly composed of Al2(SO4)3; In step S3, the nanofiltration membrane separation is multi-stage nanofiltration, the number of stages is 2-7, and the nanofiltration pressure is 2.0-8.0Mpa; The mass concentration of Li2SO4 in the monovalent ionic liquid mainly composed of Li2SO4 is 10-80g / L, and the mass concentration of Al2(SO4)3 in the multivalent ionic liquid mainly composed of Al2(SO4)3 is 10-80g / L; S4: chemically removing impurities from the monovalent ionic liquid mainly composed of Li2SO4 to obtain a de-impurified liquid and de-impurified residue; S5: subjecting the impurity-removed liquid to lithium precipitation reaction using a soda ash solution, and filtering to obtain battery-grade lithium carbonate and lithium precipitation mother liquor; S6: using a soda solution to chemically precipitate aluminum using the multivalent ion liquid mainly composed of Al2(SO4)3 to separate aluminum hydroxide and Na2SO4 solution; S7: Concentrate and crystallize the lithium precipitation mother liquor and the Na2SO4 solution to obtain Na2SO4.

2. The method according to claim 1, characterized in that: In step S2, the liquid-to-solid mass ratio of the water-added slurry is 3-6:

1.

3. The method according to claim 1, characterized in that: In step S4, the substance used for the chemical impurity removal is one or more of NaOH, LiOH and Na2CO3, the chemical impurity removal reaction end point pH is 10-12, the temperature is 50-80°C, and the time is 1-3h.

4. The method according to claim 1, characterized in that: In step S5, the lithium precipitation reaction temperature is 60-80° C., the amount of soda ash solution used is 100-110 wt % of the theoretical amount required for the precipitation reaction of Li and carbonate in the solution after impurities removal, and the lithium precipitation reaction time is 1-2 h.

5. The method according to claim 1, characterized in that In step S6, the endpoint pH value of the chemical aluminum precipitation reaction is 3-7, the temperature is 50-90° C., and the time is 1-2 hours.

6. The method according to claim 1, characterized in that In step S7, the concentration temperature is 70-110°C, and the crystallization temperature is -5-40°C.

7. The method according to claim 1, characterized in that In step S7, the impurity-removed slag in step S4 is returned to the spodumene after ball milling in step S2.

Citation Information

Cited By

  • Method for producing battery-grade lithium carbonate by using membrane method in lepidolite hydrochloric acid method

    CN116425180A

  • A method for producing battery-grade lithium carbonate by a method of spodumene hydrochloric acid process

    CN116425180B